Size and Charge Effects on Crossover of Flow Battery Reactants Evaluated by Quinone Permeabilities Through Nafion. Issue 4 (1st April 2023) - George, Thomas Y.; Kerr, Emily F.; Haya, Naphtal O.; Alfaraidi, Abdulrahman M.; Gordon, Roy G.; Aziz, Michael J.
Abstract : Organic reactants are promising candidates for long-lifetime redox flow batteries, and synthetic chemistry unlocks a wide design space for new molecules. Minimizing crossover of these molecules through ion exchange membranes is one important design consideration, but the ways in which the crossover rate depends on the structure of the crossing species remain unclear. Here, we contribute a systematic evaluation of size- and charge-based effects on dilute-solution small molecule permeability through the Nafion NR212 cation exchange membrane. We found that increasing the magnitude of charge number z with the same sign as membrane fixed charges, achieved here by successive sulfonation of quinone redox cores, results in more than an order of magnitude permeability reduction per sulfonate. Size-based effects, understood by comparing the Stokes radii of the quinones studied, also reduces permeability with increasing effective molecule size, but doubling the effective size of the redox reactants resulted in a permeability decrease of less than a factor of three.